2023
DOI: 10.1007/s10995-023-03591-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Pattern, and Outcome of Congenital Anomalies Admitted to a Neonatal Unit in a Low-Income Country—a Ten-Year Retrospective Study

Abstract: Objective The incidence of congenital abnormalities is highest in low-and-middle-income countries. However, the prevalence, spectrum, trends of neonatal congenital anomalies and their admission outcomes have not been well explored. This study was a 10 year retrospective hospital-based research in a low-income country to address the above. Methods All infants hospitalized in the Special Care Baby Unit at the Cape Coast Teaching Hospital in Ghana, between 1s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
2
1
0
Order By: Relevance
“…Globally, congenital anomalies are the fourth leading cause of neonatal mortality with an annual death of 240,000 of which 90% with serious disorders are from low-and-middle-income countries 33 . Our findings are similar to previous studies in Nigeria 34 , Ghana 35 , and South Africa 36 where congenital anomalies was found to have accounted for 10.4–33.5% of neonatal mortality of neonates admitted to NICU. Measures to promote primary prevention and improve the health of neonates with congenital disorders via improved surveillance, building capacity and increase expertise on prevention and care, increasing awareness on newborn screenings, strengthening research on major birth defects, and supporting affected families may help reduce the burden of congenital anomalies 33 .…”
Section: Discussionsupporting
confidence: 91%
“…Globally, congenital anomalies are the fourth leading cause of neonatal mortality with an annual death of 240,000 of which 90% with serious disorders are from low-and-middle-income countries 33 . Our findings are similar to previous studies in Nigeria 34 , Ghana 35 , and South Africa 36 where congenital anomalies was found to have accounted for 10.4–33.5% of neonatal mortality of neonates admitted to NICU. Measures to promote primary prevention and improve the health of neonates with congenital disorders via improved surveillance, building capacity and increase expertise on prevention and care, increasing awareness on newborn screenings, strengthening research on major birth defects, and supporting affected families may help reduce the burden of congenital anomalies 33 .…”
Section: Discussionsupporting
confidence: 91%
“…Globally, congenital anomalies are the fourth leading cause of neonatal mortality with an annual death of 240,000 of which 90% with serious disorders are from low-and-middle-income countries 33 . Our ndings are similar to previous studies in Nigeria 34 , Ghana 35 , and South Africa 36 where congenital anomalies was found to have accounted for 10.4%-33.5% of overall neonatal mortality. Measures to promote primary prevention and improve the health of neonates with congenital disorders via improved surveillance, building capacity and increase expertise on prevention and care, increasing awareness on newborn screenings, strengthening research on major birth defects, and supporting affected families may help reduce the burden of congenital anomalies 33 .…”
Section: Discussionsupporting
confidence: 91%
“…In our previous published study, in 2015, the mortality rate was significantly lower (29%) [11]. A similar rate of 36.7% and 33.4 was seen in a study in Malta [12] in 2014, and recent 10-years-retrospective study in Ghana [13], while a significantly lower rates of 10.4%, 15.4%, were seen among other studies [14][15]. There was a higher number of males, but there wasn't a significant association could between male sex and death.…”
Section: Disscusionsupporting
confidence: 70%